Metaheuristics based energy efficient task scheduling scheme for cyber-physical systems environment - Hilal, Anwer Mustafa; Hassan Abdalla Hashim, Aisha; Obayya, Marwa; Gaddah, Abdulbaset; Mohamed, Abdullah; Yaseen, Ishfaq; Rizwanullah, Mohammed; Zamani, Abu Sarwar (Multidisciplinary Digital Publishing Institute (MDPI), 2022)
The widespread applicability of cyber-physical systems (CPS) necessitates efficient schemes to optimize the performance of both computing units and physical plant. Task scheduling (TS) in CPS is of vital importance to enhance resource usage and system efficiency. Traditional task schedulers in embedded real-time systems are unable to fulfill the performance requirements of CPS because of the task diversity and system heterogeneities. In this study, we designed a new artificial rabbit optimization enabled energy-efficient task-scheduling scheme (ARO-EETSS) for the CPS environment. The presented ARO-EETSS technique is based on the natural survival practices of rabbits, comprising detour foraging and arbitrary hiding. In the presented ARO-EETSS technique, the TS process is performed via the allocation of n autonomous tasks to m different resources. In addition, the objective function is based on the reduction of task completion time and the effective utilization of resources. In order to demonstrate the higher performance of the ARO-EETSS system, a sequence of simulations was implemented. The comparison study underlined the improved performance of the ARO-EETSS system in terms of different measures.